Practical airport operations, safety, and emergency management protocols for today and the future - Price, Jeffrey C.; Forrest, Jeffrey S. (Butterworth-Heinemann, 2016)
Practical Airport Operations, Safety, and Emergency Management: Protocols for Today and the Future focuses on the airport itself, not the aircraft, manufacturers, designers, or even the pilots. The book explores the safety of what's been called 'the most expensive piece of pavement in any city'- the facility that operates, maintains, and ensures the safety of millions of air passengers every year. The book is organized into three helpful sections, each focusing on one of the sectors described in the title. Section One: Airport Safety, explores the airport environment, then delves into safety management systems. Section Two: Airport Operations, continues the conversation on safety management systems before outlining airside and landside operations in depth, while Section Three: Airport Emergency Management, is a careful, detailed exploration of the topic, ending with a chapter on the operational challenges airport operations managers can expect to face in the future. Written by trusted experts in the field, users will find this book to be a vital resource that provides airport operations managers and students with the information, protocols, and strategies they need to meet the unique challenges associated with running an airport